De l’argument à l’action : la biodiversité au service des jardins familiaux - Jean-Noël Consalès; Sophie Joimel; France Cordier; Cloé Jareno; Élodie-Denise Chenot; Christophe Schwartz (Projets de Paysage)
This article studies the relationships between allotment gardens and the notion of biodiversity. To do so, it compares two levels of analysis. On the national level, it shows that biodiversity is an integral part of the strategy developed by the National Federation of Allotment and Community Gardens (in French Fédération nationale des jardins familiaux et collectifs) in support of these urban vegetable gardens. This association facilitates projects designed to be sustainable and to provide a favourable environment for plant and animal life. At the local level, ecological surveys conducted in certain locations in Marseilles have designated allotment gardens as the reservoirs of an abundant although ordinary biodiversity. In a context of urbanisation, this often serves as an argument in favour of community garden management associations. Allotment gardens also give rise to renewed considerations and practises, but ones which are greatly marked by representations and ambiguities regarding the notion of biodiversity. As a result, the spontaneous growth of plants and animal life in the soil are the unplanned results of the vegetable garden.